2002
DOI: 10.1002/ijc.10256
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle factors and pancreatic cancer risk: A cohort study from the Swedish Twin Registry

Abstract: Dear Sir,Even though pancreatic cancer is the 5th-leading cause of cancer deaths in the Western world, 1 little is known about the etiology of the disease. Lifestyle and other risk factors for pancreatic cancer have been examined in many epidemiologic studies, most of which were case-control studies. The conclusions of many of these are dubious because of small sample size, low participation and use of proxy respondents. Only cigarette smoking stands out as a likely causal agent in epidemiologic studies. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 19 publications
4
66
1
1
Order By: Relevance
“…In studies carried out in the U.S.A., a positive relationship was demonstrated for both men and women in the 3 largest cohort studies, [15][16][17] while 4 other smaller studies found a positive association only in men. 10,22,26,33 The 6 other studies, including the 2 largest European cohort studies, 6,[18][19][20][21]35 did not find any significant association in the combined data of men and women. Similar to cohort studies, case-control studies have also produced contradictory results with a meta-analysis carried out in 2003 concluding that the risk of pancreatic cancer was only weakly associated with obesity.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In studies carried out in the U.S.A., a positive relationship was demonstrated for both men and women in the 3 largest cohort studies, [15][16][17] while 4 other smaller studies found a positive association only in men. 10,22,26,33 The 6 other studies, including the 2 largest European cohort studies, 6,[18][19][20][21]35 did not find any significant association in the combined data of men and women. Similar to cohort studies, case-control studies have also produced contradictory results with a meta-analysis carried out in 2003 concluding that the risk of pancreatic cancer was only weakly associated with obesity.…”
Section: Discussionmentioning
confidence: 87%
“…Since 2000, at least 13 prospective cohort studies carried out in Western countries have reported a link between BMI and pancreatic cancer risk, 6,10,[15][16][17][18][19][20][21][22]26,35 although the findings have been inconsistent. In studies carried out in the U.S.A., a positive relationship was demonstrated for both men and women in the 3 largest cohort studies, [15][16][17] while 4 other smaller studies found a positive association only in men.…”
Section: Discussionmentioning
confidence: 99%
“…3 To date, 11 cohort studies have investigated the relation between the intake of total meat, different meat types and eggs and pancreatic cancer risk. 3,6,[8][9][10][11][12] Two studies have observed a positive association with total meat intake, 3,11 the Multiethnic Cohort Study has observed increased risks with the intake of beef and pork, 3 and a cohort among 7th-day Adventists has observed a positive association with egg intake. 3 Inverse associations were observed with the intake of pork in a study of Swedish twins 8 and with the intake of poultry among Swedish women.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Since then, numerous epidemiological studies have investigated the relation between meat, eggs, and different types of fat and pancreatic cancer, including 15 prospective cohort studies 3,6,[8][9][10][11][12] and 31 case-control studies. 3,6,[13][14][15][16][17][18][19] In a recent Expert Panel Report, it was concluded that there is limited evidence suggesting that red meat is a cause of pancreatic cancer in humans.…”
Section: -5mentioning
confidence: 99%
“…The association between meat intake and pancreatic cancer has been examined in both case control and cohort (23)(24)(25)(26)(27)(28)(29)(30)(31)(32) studies with positive (2-7, 9-12, 22-27), inverse (13)(14)(15)28), and null (4, 5, 8, 14-21, 29, 32) associations reported for both study designs. The inconsistent results among case-control studies may partly be due to retrospective ascertainment of diet, which, given the rapid fatality of pancreatic cancer, may be fraught with biases, such as recall and proxy, and reverse causation.…”
Section: Introductionmentioning
confidence: 99%